Natural compounds and combination therapy in colorectal cancer treatment - Rejhová, A; Opattová, A; Čumová, A; Slíva, D; Vodička, P (European journal of medicinal chemistry, 2018)
Colorectal cancer (CRC) therapy using conventional chemotherapeutics represents a considerable burden for the patient's organism because of high toxicity while the response is relatively low. Our review summarizes the findings about natural compounds as chemoprotective agents for decreasing risk of CRC. It also identifies natural compounds which possess anti-tumor effects of various characteristics, mainly in vitro on colorectal cell lines or in vivo studies on experimental models, but also in a few clinical trials. Many of natural compounds suppress proliferation by inducing cell cycle arrest or induce apoptosis of CRC cells resulting in the inhibition of tumor growth. A novel employment of natural substances is a so-called combination therapy - administration of two or more substances - conventional chemotherapeutics and a natural compound or more natural compounds at a time. Some natural compounds may sensitize to conventional cytotoxic therapy, reinforce the drug effective concentration, intensify the combined effect of both administered therapeutics or exert cytotoxic effects specifically on tumor cells. Moreover, combined therapy by targeting multiple signaling pathways, uses various mechanisms to reduce the development of resistance to antitumor drugs. The desired effect could be to diminish burden on the patient's organism by replacing part of the dose of a conventional chemotherapeutic with a natural substance with a defined effect. Many natural compounds are well tolerated by the patients and do not cause toxic effects even at high doses. Interaction of conventional chemotherapeutics with natural compounds introduces a new aspect in the research and therapy of cancer. It could be a promising approach to potentially achieve improvements, while minimizing of adverse effects associated with conventional chemotherapy.
Keywords: biologické přípravky; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Oxaliplatin; kolorektální nádory; Adverse effect; Chemotherapy; Colorectal Neoplasms; Cell Proliferation; 5-Fluorouracil; Combination therapy; zvířata; vztahy mezi strukturou a aktivitou; Humans; molekulární struktura; Antineoplastic Combined Chemotherapy Protocols; proliferace buněk; Apoptosis; protokoly protinádorové kombinované chemoterapie; Drug resistance; Biological Products; Cell proliferation; Structure-Activity Relationship; Natural compound; lidé; Colorectal cancer; Molecular Structure; Animals